Ethics-Based Teacher Recruitment: A Philosophical Reflection on the Non-Smoking Policy at MIS Nurul Amal - Titim Marlika; Akhmad Affandi; Tamsik Udin (PT. Student RIhlah Indonesia, 2026)
This study examines the ethics-based teacher recruitment policy at MIS Nurul Amal, particularly the non-smoking requirement for male teachers, as an institutional embodiment of moral values in Islamic education. Employing a qualitative case study approach, data were collected through interviews, observations, and documentation. The findings reveal that the policy fosters not only a healthy and religious school climate but also a culture of moral exemplarity embedded in teachers’ daily conduct. The analysis incorporates the Islamic concept of uswah hasanah and Sartrean existential ethics concerning individual moral responsibility. The study proposes a conceptual model of character formation through ethical recruitment, offering a replicable framework for other values-based educational institutions.